ANALYSIS OF FUEL RETAILERS’ PERSPECTIVE ON THE USE OF MEASURING MACHINES AND THE ACCURACY OF THE DOSE ACCORDING TO THE CONCEPT OF MABI’ - Syuhada; Nurdin Bakri; Nurul Fithria (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2025)
In buying and selling transactions, Mabi’ is the core object involved between the seller and the buyer. Mabi’ can be goods offered by the seller and paid for by the buyer with money or a certain value. Sellers must also establish clear procedures, such as proper measurements or scales, to ensure the product has resale value and is attractive to buyers. The focus of this research is the use of electric measuring devices in retail fuel sales at gas stations, especially in filling Pertalite and Pertamax. This research employs an empirical juridical approach, where interviews are a primary method for gathering relevant data. The research results show that accurate measuring tools, such as a 3.5-meter-long hose, are crucial for ensuring accurate measurements in retail fuel dispensing. Traders need to know the accuracy of the measuring equipment used so that retail fuel filling is conducted within the provisions of the measuring machine. In this case, Mabi’ not only involves sellers and buyers, but also includes the role of supervisor or regulator to ensure transactions are carried out fairly and according to standards. Honesty, integrity, and accountability are crucial for maintaining the quality and accuracy of retail fuel buying and selling transactions, which ensures buyer satisfaction and seller profits.